2018
DOI: 10.1002/adma.201800754
|View full text |Cite
|
Sign up to set email alerts
|

Black Arsenic: A Layered Semiconductor with Extreme In‐Plane Anisotropy

Abstract: Abstract2D layered materials have emerged in recent years as a new platform to host novel electronic, optical, or excitonic physics and develop unprecedented nanoelectronic and energy applications. By definition, these materials are strongly anisotropic between the basal plane and cross the plane. The structural and property anisotropies inside their basal plane, however, are much less investigated. Black phosphorus, for example, is a 2D material that has such in‐plane anisotropy. Here, a rare chemical form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
222
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 188 publications
(235 citation statements)
references
References 36 publications
13
222
0
Order By: Relevance
“…In the monolayer limit, the performance shows relatively high carrier mobilities and large on/off ratios. [22,23] A recent paper reported that black arsenic is metastable and often stabilized by impurities; and it is very difficult to synthesize the purity black arsenic under the lab conditions. The few-layer arsenic based FET still function after exposure to air for about one month.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In the monolayer limit, the performance shows relatively high carrier mobilities and large on/off ratios. [22,23] A recent paper reported that black arsenic is metastable and often stabilized by impurities; and it is very difficult to synthesize the purity black arsenic under the lab conditions. The few-layer arsenic based FET still function after exposure to air for about one month.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] This characteristic leads it to a possibility for applications in optoelectronic and logical devices. [22,23] A recent paper reported that black arsenic is metastable and often stabilized by impurities; and it is very difficult to synthesize the purity black arsenic under the lab conditions. [20,21] These excellent physical properties make it a good candidate for applications in electronic devices.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both theoretical and experimental characterization have demonstrated that B‐As is a layered material similar to B‐P, and the band structure is related to the number of layers. The bulk B‐As bandgap is about 0.3 eV, which is a direct bandgap; the single layer is about 1.5 eV, which is an indirect bandgap . Most importantly, B‐As has a stronger anisotropy .…”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 99%